Tin dodecamers and radiation patternable coatings with strong EUV absorption
Patent Information
- Application Number
- JP2024135624
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2018-04-05
- Filing Date
- 2024-08-15
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2039-04-04
AI Technical Summary
Existing semiconductor processing technologies face challenges in achieving high-resolution patterning of small features due to the reduced critical dimensions in integrated circuits, requiring new materials and methods that can effectively absorb extreme ultraviolet (EUV) light and electron beam radiation for improved etching contrasts.
The development of alkyltin clusters, specifically tin dodecamers, which are formulated as radiation patternable coatings, utilizing alkyl ligands with tin atoms to enhance EUV absorption and stability, and incorporating fluorinated species to improve solubility contrast and reduce unwanted chemical reactions.
The alkyltin dodecamers exhibit high EUV absorption, reducing defects and improving patterning fidelity, enabling the formation of fine features with smooth edges and high resolution, suitable for advanced semiconductor manufacturing.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to co-pending U.S. Provisional Patent Application No. 62 / 653,043, filed April 5, 2018, to Cardineau et al., entitled “Photoresists With High EUV Absorption,” which is incorporated herein by reference.
[0002] The present invention relates to alkyltin clusters suitable for forming radiation patternable coatings. The present invention further relates to alkyl ligands having tin atoms incorporated therein. [Background technology]
[0003] Extreme ultraviolet (EUV) lithography is a method for producing high performance integrated circuits containing densely patterned structures on the nanoscale. To produce these circuits, photoresist is deposited on a substrate and exposed to a pattern of EUV light. The exposed areas undergo radiolysis, changing their solubility, which allows for precise transfer of the EUV light pattern into the resist after solvent development and further processing. The developed photoresist pattern is then transferred to the underlying substrate by an etching process. Summary of the Invention [Problem to be solved by the invention]
[0004] The fabrication of semiconductor circuits and devices has been accompanied by a continuing reduction in critical dimensions with each generation. These reductions in dimensions may require new materials and methods to meet the processing and patterning requirements of ever smaller features. Patterning generally involves the selective exposure of a thin layer of radiation-sensitive material (resist) to form a pattern, which is then transferred to a subsequent layer or functional material. A new class of promising metal-based radiation resists has been discovered that are particularly suitable for obtaining good absorption of extreme ultraviolet (EUV) light and electron beam radiation while at the same time obtaining very high etch contrast. To obtain smaller patterned features, EUV has proven to be an important tool in the fabrication of semiconductors, and resist compositions that can take advantage of EUV may be valuable components to this endeavor. [Means for solving the problem]
[0005] In a first aspect, the present invention provides a compound of formula (QSn) 12 O 14 (OH)6(RCO2)2, where R is H or an alkyl group having 1 to 10 carbon atoms and Q is a hydrocarbyl group having 3 to 31 total carbon atoms, or Q is a group having the structure -(CH2) n Sn(R1R2R3), where n=1-4, is an alkyltin group having 4-15 total carbon atoms, and R1, R2, and R3 are independently alkyl groups having 1-5 carbon atoms. In some embodiments, the solvent for forming the radiation patternable coating can include an organic solvent, and the composition includes a tin dodecamer.
[0006] In a further aspect, the present invention provides a compound having the formula (RCC)3SnQ, where R is a hydrocarbyl group having 1 to 15 carbon atoms and Q is the structure -(CH2) nAn alkyltin group having Sn(R1R2R3), having 4 to 15 total carbon atoms, where n = 1 to 4, and R1, R2, and R3 are each independently an alkyl group having 1 to 5 carbon atoms), and relates to a composition containing a tin compound represented by
[0007] In a further aspect, the present invention is a method for forming an organotin compound comprising: A step of gradually adding tin dihalide to a solution containing an organic solvent, alkylacetylene, and alkylmagnesium halide to form a tin intermediate solution; A step of mixing XCH2Sn(R1R2R3) (where X is a halide and R1, R2, and R3 are each independently an alkyl group having 1 to 5 carbon atoms) with the above tin intermediate solution to form (RCC)3SnCH2Sn(R1R2R3) of a solid compound, And relates to a method comprising
[0008] In another aspect, the present invention is (QSn) n O 3n / 2-1 / 2x-1 / 2y F x (OH) y , 1 ≦ n ≦ 12, (0 < x + y ≦ 8), and (Q is an alkyl group having 1 to 16 carbon atoms, or an alkyltin group having a structure -CH2Sn(R1R2R3) having 4 to 15 total carbon atoms, and R1, R2, and R3 are each independently an alkyl group having 1 to 5 carbon atoms), and relates to a composition containing the same. In some embodiments, the solution for forming a radiation patterning capable coating can include an organic solvent and this composition containing a fluorinated tin dodecamer.
[0009] In another aspect, the present invention is of the formula (QSn) 12 O 14 (OH)6(HCO2)2 (where Q is an alkyl group having 5 to 16 total carbon atoms, or Q is a structure -(CH2) nThe present invention relates to a method for fluorinating a dodecamer tin composition having the formula: Sn(R1R2R3), where n=1-4 and R1, R2, and R3 are independently alkyl groups having 1-10 carbon atoms, comprising reacting an alkyltin hydroxide with a trialkylamine trihydrofluoride. [Brief description of the drawings]
[0010]
Figure 1
Figure 2
Figure 3
Figure 4
Figure 5
Figure 6
Figure 7
Figure 8
Figure 9
Figure 10
Figure 11
[0011] Alkyl tin clusters offer promising properties for radiation-based patterning, and the tin dodecamers described herein can be suitably processed for EUV patterning of tin. A synthetic method is described herein for synthesizing dodecamers from alkyl tin triacetylide monomers. Also described herein are alkyl groups with tin ligands that can be used to effectively convert triacetylide monomers into dodecamer embodiments that also have additional tin atoms in the ligands. Tin dodecamers have oxo, hydroxo, and formate ligands, some of which are crosslinked to stabilize the cluster. Methods are disclosed for replacing the formate and / or hydroxide ligands with fluoride ions. Tin dodecamer clusters are solid compounds that are soluble in suitable organic liquids. Patterning formulations based on stabilized tin dodecamers are described. Based on these tin clusters with higher tin content, coatings formed from the tin compositions exhibit high EUV absorption.
[0012] EUV sources generally produce lower light intensities than other DUV and UV laser systems and lamps used in lithography. At this lower intensity, undesirable defects can form in the resist pattern due to EUV shot noise and the random nature of chemical reactions in the photoresist. These stochastic events occur less frequently in photoresists, which strongly absorb EUV radiation and undergo chemical changes that effectively result in a higher solubility contrast between exposed and unexposed areas.
[0013] A thin photoresist provides the highest fidelity pattern for transfer to the underlying substrate. Therefore, an effective EUV photoresist should have a very large EUV absorption cross-section so that both defectivity and writing speed can be improved. Meyers et al. in U.S. Pat. No. 9,310,684, entitled "Organometallic Solution Based High Resolution Patterning Compositions," incorporated herein by reference, describe novel organotin photoresist compositions with high absorption coefficients for EUV lithography. The solution coating and film compositions include tin bonded by alkyl groups and further bridged by oxo (O) and / or hydroxo (-OH) groups. Here, we describe novel compositions exemplified by replacing C, O, and -OH groups with stronger EUV absorbing species. The carbon atom C in the alkyl chain can be replaced by Sn, and O and -OH can be replaced by F. A comparison of the cross sections in Table 1 shows that greater EUV absorption can be obtained with these substitutions based on reported atomic absorption data (http: / / henke.lbl.gov / optical_constants / pert_form.html). In Table 1, absorption is in cm at 13.5 nm EUV light. 2 Reported in units per atom.
[0014] [Table 1]
[0015] Substitution of OH groups with F also limits condensation that can occur when hydroxotin species bind and HO is released, which can improve photoresist solution stability and reproducible patterning performance.
[0016] Tin clusters have been synthesized that ensure high EUV absorption while maintaining good coating properties and solution processing. Tin trimers and other clusters have been previously described in co-pending U.S. patent application Ser. No. 16 / 194,491 (hereinafter the '491 application) to Cardineau et al., entitled "Organotin Clusters, Solutions of Organotin Clusters, and Application to High Resolution Patterning," which is incorporated herein by reference. The '491 application teaches the use of alkyltin trialkylacetylide monomers, particularly alkyltin triphenylacetylide monomers, to form clusters. In some embodiments, these monomers are used to form the dodecamers described herein. Tin dodecamers with structures useful for resist processing, such as the two exemplary tin dodecamers, are described as providing high EUV absorption.
[0017] Dodecamer (QSn) 12 O 14 (OH)6(RCO2)2 (Q=alkyl or alkyltin ligand and R=alkyl group or H) is a representative organotin cluster formulated as a metal oxide EUV photoresist. Also, the carboxylate, e.g., formate, and possibly some or all of the hydroxide ligands can be replaced by fluoride ions, as described below. The Q ligands can generally have a quaternary carbon atom or a tin atom. In the case of alkyl groups having quaternary carbon atoms, these alkyl groups have generally been found to produce desirable patterned coatings, and these ligands can generally have 5-17 carbon atoms. Alkyltin ligands have a tin atom in place of the quaternary carbon of the analogous alkyl group, and can contain 4-16 carbon atoms. Ligands in which the quaternary carbon is replaced with Sn still provide the dodecamer C-Sn bond in the above formula, Sn-(CH2) nA -Sn moiety is formed, where n is 1 to 4. Substitution of a quaternary carbon can be advantageous for EUV lithography because Sn has a wider EUV absorption cross section than C (see Table 1).
[0018] Tin Cluster (BuSn) 12 O 14 (OH)6 +2 and (i-PrSn) 12 O 14 (OH)6 +2 The synthesis of these nanobuilding blocks was reported by Eychenne-Baron et al. (hereafter referred to as Eychenne-Baron), “New synthesis of the nanobuilding block {(BuSn) 12 O 14 (OH)6} 2+ and exchange properties of {(BuSn) 12 O 14 (OH)6}(O3SC6H4CH3)2,” J. Organometallic Chemistry 1998, 567, 137-142, and Puff et al. Kaefig-ion[(i-PrSn) 12 O 14 (OH)6 +2 ],” J. Organometallic Chemistry 1989, 373, 173-184, both of which are incorporated herein by reference. Described herein are highly specific synthetic methods for the formation of the aforementioned compositions bearing sterically bulky neopentyl-based alkyl ligands (optionally substituted with quaternary tin atoms) that have been found to adequately stabilize the clusters, and for the introduction of formate anions.
[0019] Puff describes the isolation of those compounds that have a chloride anion and associate with a solvent molecule (water, or water with DMF (dimethylformamide) or DMPU (N,N'-dimethylpropyleneurea). Eychenne-Baron has investigated the substitution of the as-synthesized compound with a p-toluenesulfonyl anion and has succeeded in partially replacing that group with an acetate group. The synthetic method of the present invention allows the preparation of dodecamers as formate salts with alternative alkyl substituents.
[0020] It has been found that medium sized branched alkyl ligands provide good patterning performance. * The simplest alkyl group containing the atom is neopentyl (CH3)3C * The neopentyl moiety has the structure CH2-, which can be called a t-amyl group. * (CH2) n where n is an integer from 1 to 4 (i.e., 1, 2, 3, or 4), but generally C * is simply written as C, " * " is used simply to introduce the concept of quaternary carbon. The generalized groups maintain the same ligand bond with an optionally extended alkyl structure. In general, the R1, R2, and R3 moieties may independently be groups having 1 to 5 carbon atoms, such as methyl (CH3-), ethyl (CH3CH2-), etc. Quaternary C * by Sn to give the corresponding alkyl tin ligand (CH3)3SnCH2- or generally (R1R2R3)Sn(CH2) n -, where n is an integer from 1 to 4, and R1, R2, and R3 are as previously described. Alternative branched alkyl groups such as tert-butyl ((CH3)3C-), sec-butyl (CH3CHCH2CH3), isobutyl (CH3)2CHCH2-, isopropyl ((CH3)2CH-) may be desirable, and in some embodiments unbranched alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, and larger groups may be desirable.
[0021] Ligands with quaternary carbon or tin centers have been found herein to be useful for binding to the Sn atom to form monomers for the ultimate synthesis of the dodecamer. These monomers generally have the structure QSn(C6H5CC)3, where Q in the phenylacetylide is an alkyl or alkyltin ligand of the cluster. The monomer (CH3)3SnCH2Sn(C6H5CC)3 is exemplified below and is believed to be the first example of a monoalkyloxo-hydroxotin species in which the C in the alkyl group is replaced with Sn. This monomer can be further modified using another alkyl ligand substituent -(CH2) n (C6H5CC)3Sn(CH2) with 5 to 16 total carbon atoms in the C(R1R2R3) ligand n C(R1R2R3) or -(CH2) n (C6H5CC)3Sn(CH2) with 4 to 15 total carbon atoms in the Sn(R1R2R3) ligand n Sn(R1R2R3), where n=1, 2, 3, or 4, and R1, R2, and R3 are independently linear or branched alkyl groups having 1-5 carbon atoms. Trialkyl acetylide monomers can also be generalized with different substituents as (R'CC)3SnQ, where R' is an organic group having 1-15 carbon atoms, such as an alkyl group, an alkenyl group, an aromatic group, the corresponding halogenated species, or derivatives thereof.
[0022] The aforementioned trialkylacetylide monomers can be converted to dodecameric (QSn) monomers by hydrolysis and condensation under appropriate conditions. 12 O 14It forms (OH)6(HCO2)2, where Q can include a tin atom. Solutions of this dodecamer in organic solvents can be easily deposited into thin films by spin coating or other suitable processing. Based on the reported atomic EUV absorption cross sections, a film thickness of 25 nm, and a packing density comparable to that of a neopentyltin dodecamer film, a film with alkytin ligands is expected to absorb approximately 1.5 times as many EUV photons as the corresponding neopentyl system. Analysis of the corresponding EUV exposure sequences shows desirable performance, as described in the Examples below. The dodecamer compounds are solids and generally crystalline. ((CH3)3CSn) 12 O 14 The crystal structure of (OH)6(HCO2)2 is shown in the Examples below.
[0023] Each R (alkyl) group is individually bonded to the tin atom and generally has 1-31 carbon atoms, with 3-31 carbon atoms in a group having secondary bonded carbon atoms and 4-31 carbon atoms in a group having tertiary bonded carbon atoms, although in some embodiments each R group can have 20 or fewer carbon atoms, and in further embodiments 15 or fewer carbon atoms. A person of ordinary skill in the art will recognize that additional ranges of carbon numbers within the explicit ranges above are contemplated and are within the scope of the present disclosure. In particular, the R-Sn portion of the cluster can be denoted by R 1 R 2 R 3 CSn, and R 1 and R 2 are independently alkyl groups having 1 to 10 carbon atoms, and R 3 For some patterning compositions where R is hydrogen or an alkyl group having 1 to 10 carbon atoms, branched alkyl ligands may be desirable. 1 and R 2 can form a cyclic alkyl moiety, R 3 can also be linked to another group on the cyclic moiety. Suitable branched alkyl ligands are, for example, isopropyl (R 1 and R 2is methyl and R 3 is hydrogen), tert-butyl (R 1 , R 2 , and R 3 is methyl), tert-amyl (R 1 and R 2 is methyl and R 3 is -CH2CH3), sec-butyl (R 1 is methyl and R 2 is -CH2CH3, and R 3 is hydrogen), neopentyl (R 1 and R 2 is hydrogen and R 3 is -C(CH3)3), cyclohexyl, cyclopentyl, cyclobutyl, and cyclopropyl. Examples of suitable cyclic groups include, for example, 1-adamantyl (-C(CH2)3(CH)3(CH2)3 or tricyclo(3.3.1.13,7)decane attached to the metal at a tertiary carbon) and 2-adamantyl (-CH(CH)2(CH2)4(CH)2(CH2) or tricyclo(3.3.1.13,7)decane attached to the metal at a secondary carbon). In another embodiment, the hydrocarbyl group can include an aryl or alkenyl group, such as a benzyl or allyl group, or an alkynyl group. In another embodiment, the hydrocarbyl ligand R can include any group consisting of only C and H and containing 1 to 31 carbon atoms. For example, linear or branched alkyl (i-Pr((CH3)2CH-), t-Bu((CH3)3C-), Me(CH3-), n-Bu(CH3CH2CH2CH2-)), cycloalkyl (cyclopropyl, cyclobutyl, cyclopentyl), olefin (alkenyl, aryl, allyl), or alkynyl groups, or combinations thereof. In further embodiments, suitable R groups can include hydrocarbyl groups substituted with heteroatom functional groups such as cyano, thio, silyl, ether, keto, ester, or halogenated groups, or combinations thereof.
[0024] The synthesis of triacetylide tin monomers is discussed in the aforementioned '491 application and in the Examples below. As previously mentioned, the monomers are alkyl or alkyltin trialkylacetylides. In particular, the '491 application describes the synthesis of t-butyltin triphenylacetylide based on the reaction of phenylacetylene with t-butyltin tris(dimethylamide). Generally, alkyltin acetylides are prepared by reacting the alkyl acetylide anion (R'C≡C - ) to RSnCl3, addition of an alkyl anion to Sn(C≡CR″4, or reaction of HC≡CR″ with RSn(NR′″2)3. The acetylide anion can be formed with a very strong base to form the compound RC≡CM with the appropriate cation, where M is lithium, sodium, potassium, magnesium halide [MgX]. + , zinc halide [ZnX] + (X=halide), or another ion with an electropositive metal.
[0025] With respect to the synthesis of alkyltin tin trialkylacetylides in the examples herein, the reaction can be carried out with an alkylacetylene, such as phenylacetylene, which is reacted with a superbase, such as isopropylmagnesium chloride, in an organic solvent to form an organometallic alkylacetylide. Suitable organic solvents include tetrahydrofuran and other polar non-reactive solvents, which are generally aprotic. After reaction of the alkylacetylene with the superbase, a tin dihalide dissolved in an organic solvent is added, and the solution is allowed to react at room temperature for at least 1 hour. A (haloalkyl)trialkylstannane is then added to the reaction mixture, and the reaction is allowed to proceed for at least 5 minutes, which can be carried out at room temperature. Using the notation above, the haloalkyl group is the -(CH2) of the monomer. nThe trialkyl groups of the stannane become the R1, R2, and R3 moieties of the monomer. The product alkyltin tintrialkylacetylide forms a solid precipitate which can be collected and washed. The product can be further crystallized by recrystallization from a hydrocarbon solvent such as pentane or hexane.
[0026] The synthesis of the dodecamer is initiated by first adding a small amount of water to an organic solution of the monomers. Suitable organic solvents include, but are not limited to, alcohol or tetrahydrofuran, although many organic solvents will generally be suitable. Water is added in approximately stoichiometric amounts to obtain one water molecule for each alkyl acetylide ligand. This initial reaction is carried out for at least one hour and can be carried out for several days at room temperature, with three days of reaction in the examples. This initial reaction is believed to involve the formation of the dodecamer in the hydroxide form. After completion of this initial reaction, a carboxylic acid is added to the product of the initial reaction, and the solution may or may not be heated to boiling before the carboxylic acid is added. The following examples are carried out using formic acid. The carboxylic acid can generally be added gradually and in approximately stoichiometric amounts. After the formic acid is added, the solution is stirred for an additional time, generally at least one minute or more. The resulting solid product can be collected and washed. It may be desirable to recrystallize the product.
[0027] The dodecameric (t-BuSn) can be obtained by reaction with trialkylamine trihydrofluorides, e.g., triethylamine [(CH2CH2)3N 3HF]. 12 O 14 (OH)6(HCO2)2, or more commonly the dodecameric form (QSn) 12 O 14The formate and / or hydroxide ions or a portion thereof in (OH)6(HCO2)2 can be replaced with fluoride ions, where Q is an alkyl or tin alkyl ligand as described above. Ammonium bifluoride (NH4HF2) or other HF sources can be used in place of trialkylamine trihydrofluoride. In one example below, the dodecameric (t-BuSn) 12 O 14 The replacement of six hydroxides and two formates with eight fluorides by reaction with triethylamine trihydrofluoride to form F8 is described. It is believed that this replacement was previously unknown in monoalkyloxo-hydroxotin dodecamer chemistry. Chemical and NMR analysis confirm the complete replacement of hydroxides and formates with fluorides. Mass spectrometry analysis indicates that partial replacement is also possible. Solutions of the fluoride dodecamers in suitable organic solvents can be spin-coated as thin films suitable for EUV exposure. Analysis of the exposure sequence reveals excellent performance as described in the examples below.
[0028] The use of alkyl-substituted metal coordination compounds in high performance radiation-based patterning compositions is described, for example, in U.S. Patent No. 9,310,684 to Meyers et al., entitled "Organometallic Solution Based High Resolution Patterning Compositions," which is incorporated herein by reference. Improvements to these organometallic compositions for patterning are described in U.S. Patent Application Publication No. 2016 / 0116839 A1 to Meyers et al., entitled "Organometallic Solution Based High Resolution Patterning Compositions and Corresponding Methods," and U.S. Patent Application Publication No. 2017 / 0102612 A1 to Meyer et al., entitled "Organotin Oxide Hydroxide Patterning Compositions, Precursors, and Patterning," both of which are incorporated herein by reference. The organometallic compositions in these references have structures based on one metal moiety. The metal clusters described herein contain bridging groups between two or three metal atoms. Metal cluster based compositions can be effectively used for patterning and potentially have processing advantages.
[0029] To form a resist precursor solution, the cluster composition can be dissolved in a suitable organic solvent. It has been found to be soluble in chloroform, ketones, alcohols, and a series of polar organic solvents. The alcohol can be one or more of 1-methoxy-2-propanol, 4-methyl-2-pentanol, cyclopentanol, methanol, ethanol, n-propanol, or isopropanol, mixtures thereof, and the like. Suitable alcohols include, for example, alkoxy alcohols having 4 to 10 carbon atoms. Suitable solvents also include, for example, propylene glycol methyl ether acetate, and the like. The alkyl tin dodecamer composition is also soluble in a solution having one or more of polar ethers, such as tert-butyl methyl ether and anisole, ethyl lactate, cyclic ethers, such as tetrahydrofuran, and the like. Other organic solvents based on the above specific solvents may also be suitable. The concentration of tin can be in the range of about 1 mM to about 1 M, in further embodiments about 2 mM to about 750 mM, and in other embodiments about 5 mM to about 500 mM, based on the amount of tin. For most solvents, it may be desirable to add a carboxylic acid to the solution to stabilize the cluster composition with its carboxylate anion. Formic acid or other carboxylic acids can be added as stabilizers at concentrations of about 1%-30% v / v, and in further embodiments about 5%-20% v / v, which is the volume added per total volume of the mixture. In general, the choice of organic solvent can be influenced by solubility parameters, volatility, flammability, toxicity, viscosity, and potential chemical interactions with other processing materials. Those skilled in the art will appreciate that additional concentration ranges within the ranges explicitly stated above are contemplated and are within the scope of the present disclosure. In general, the precursor solution can be mixed thoroughly using suitable mixing equipment appropriate for the formation of the volume of material. Appropriate filtration can be used to remove any contaminants or other components that do not dissolve properly.
[0030] The coating material can be formed by deposition of the precursor solution on a selected substrate and subsequent processing. With the precursor solutions described herein, some hydrolysis and condensation may occur during coating, and subsequent processing steps, such as heating in air, may complete or accelerate post-coating. The substrate generally provides a surface onto which the coating material can be deposited, and the substrate may include multiple layers, in which the surface is associated with the top layer. In some embodiments, the substrate surface may be treated to prepare the surface for adhesion of the coating material. The surface may also be cleaned and / or smoothed as necessary. Suitable substrate surfaces may include any reasonable material. Some substrates of particular interest include, for example, silicon wafers, silica substrates, other inorganic materials such as ceramic materials, polymeric substrates such as organic polymers, composites thereof, and combinations thereof across the surface of the substrate and / or in multiple layers. Wafers, such as relatively thin cylindrical structures, may be convenient, although structures of any reasonable shape may be used. Polymer substrates, or substrates having a polymer layer on a non-polymeric structure, may be desirable for certain applications based on lithographic performance, or substrate cost and flexibility, and suitable polymers can be selected based on the relatively low processing temperatures that can be used to process the patternable materials described herein. Suitable polymers can include, for example, polycarbonates, polyimides, polyesters, polyalkenes, copolymers thereof, and mixtures thereof. In general, especially for high resolution applications, it is desirable for the substrate to have a flat surface. However, in certain embodiments, the substrate can have a substantial topography that is intended to be filled or planarized by the resist coating for certain patterning applications.
[0031] Generally, any suitable solution coating process can be used to deliver the precursor solution to the substrate. Suitable coating methods include, for example, spin coating, spray coating, dip coating, knife edge coating, deposition such as chemical vapor deposition (CVD) or atomic layer deposition (ALD) methods, printing methods such as inkjet printing and screen printing, etc. In some of these coating methods, a pattern of the coating material is formed during the coating process, but the resolution currently available, such as with printing, has a much lower level of resolution than that available with radiation-based patterning as described herein.
[0032] When patterning is performed using radiation, spin coating can be a desirable method to cover the substrate relatively uniformly, although edge effects may occur. In some embodiments, the wafer can be spun at a speed of about 500 rpm to about 10,000 rpm, in further embodiments about 1000 rpm to about 7500 rpm, and in further embodiments about 2000 rpm to about 6000 rpm. The spin speed can be adjusted to obtain a desired coating thickness. Spin coating can be performed for a time of about 5 seconds to about 5 minutes, and in further embodiments about 15 seconds to about 2 minutes. An initial slow speed spin, for example at 50 rpm to 250 rpm, can be used to spread the majority of the composition across the substrate initially. A backside rinse, edge bead removal step, etc., can be performed using water or other suitable solvent to remove edge bead. A person of ordinary skill in the art will understand that additional ranges of spin coating parameters within the above explicit ranges are contemplated and are within the scope of the present disclosure.
[0033] The thickness of the coating can generally be a function of the precursor solution concentration, viscosity, and spin coating rotation speed. For other coating processes, the thickness can generally also be adjusted by selecting the coating parameters. In some embodiments, the use of a thin coating may be desirable to facilitate the formation of small, high-resolution features in a subsequent patterning process. For example, the coating material after drying can have an average thickness of about 10 microns or less, in other embodiments about 1 micron or less, in further embodiments about 250 nanometers (nm) or less, in further embodiments about 1 nanometer (nm) to about 50 nm, in other embodiments about 2 nm to about 40 nm, and in some embodiments about 3 nm to about 35 nm. A person of ordinary skill in the art will recognize that additional ranges of thickness within the above stated ranges are contemplated and are within the scope of the present disclosure. The thickness can be assessed using non-contact methods of X-ray reflectivity and / or ellipsometry based on the optical properties of the film. Generally, the coating is relatively uniform for ease of processing. In some embodiments, the coating thickness varies by no more than ±50% from the average coating thickness, in further embodiments no more than ±40% relative to the average coating thickness, and in further embodiments no more than about ±25%. In some embodiments, such as highly uniform coatings on larger substrates, the coating uniformity assessment can be evaluated with a one centimeter edge exclusion, i.e., the coating uniformity is not assessed for the portion of the coating within a one centimeter edge. A person of ordinary skill in the art will recognize that additional ranges within the above explicit ranges are contemplated and are within the scope of the present disclosure.
[0034] In many coating processes, the coating process itself may cause some evaporation of the solvent, as droplets or other forms of coating material are formed and evaporation is stimulated by the larger surface area and / or movement of the solution. As the solvent is reduced, the viscosity of the coating material tends to increase, as the concentration of chemical species in the material increases. One objective during the coating process may be to remove enough solvent to stabilize the coating material for further processing. The coating species may form chemically modified coating materials by reaction with air, hydrolysis, or condensation during coating or subsequent heating.
[0035] Generally, prior to exposure to radiation, the coating material can be exposed to the presence of atmospheric moisture and optionally heated to hydrolyze hydrolyzable bonds to the metals in the precursor composition and / or to further remove the solvent to promote densification of the coating material. The coating material after in situ hydrolysis can generally form polymeric metal oxo-hydroxo and / or carboxylato networks based on the bonding of oxo-hydroxo and / or carboxylato ligands to the metals (which metals also have some alkyl ligands), or can form molecular solids composed of polynuclear metal oxo / hydroxo and / or carboxylato species with alkyl ligands.
[0036] The hydrolysis / solvent removal process may or may not be quantitatively controlled with respect to the exact stoichiometry of the heated coating material and / or with respect to the specific amount of solvent remaining in the coating material. Additionally, the formulas and compositions set forth herein may include some additional water, either directly bonded to Sn or as a hydrogen-bonded component of the network. In general, experimental evaluation of the properties of the resulting coating material may be performed to select effective processing conditions for the patterning process. While heating may not be required for the process to be successful, it may be desirable to heat the coated substrate to speed processing and / or to increase the reproducibility of the process and / or to promote evaporation of hydrolysis by-products. In embodiments where heat is applied to remove the solvent during the pre-exposure bake, the coating material may be heated to a temperature of about 45° C. to about 250° C., and in further embodiments, about 55° C. to about 225° C. Heating for solvent removal may generally be performed for at least about 0.1 minutes, in further embodiments, from about 0.5 minutes to about 30 minutes, and in further embodiments, from about 0.75 minutes to about 10 minutes. A person of ordinary skill in the art will recognize that additional ranges of heating temperatures and times within the explicit ranges above are contemplated and are within the present disclosure. As a result of the heat treatment, hydrolysis, and densification of the coating material, the coating material can exhibit an increase in refractive index and radiation absorption without significant loss of contrast.
[0037] After condensation, drying, and optional hydrolysis, radiation can be used to form fine patterns in the coating material. As mentioned above, the composition of the precursor solution, and therefore the corresponding coating material, can be designed to sufficiently absorb the desired form of radiation, with EUV radiation being of particular interest. Absorption of radiation provides energy that can break the bonds between the metal and the alkyl ligands, such that at least some of the alkyl ligands are no longer available to stabilize the material. With alkyltin ligands, the modifications caused by radiation may be less pronounced, but it is confirmed that the composition provides good patterning properties. Similarly, absorption of radiation can also cause the breaking of bonds between the metal and the carboxylate ligands, and / or the decomposition of the carboxylate ligands. Radiation decomposition products, including alkyl ligands or other fragments, may or may not diffuse out of the film, depending on process variables and the type of such products. Upon absorption of a sufficient amount of radiation, the exposed coating material condenses, i.e., forms a strengthened metal oxo-hydroxo network, which may include additional water absorbed from the ambient atmosphere. The radiation may generally be delivered according to a selected pattern. The radiation pattern is transferred to a corresponding pattern or latent image in the coating material having irradiated and non-irradiated areas. The irradiated areas include chemically altered coating material, while the non-irradiated areas generally include the as-formed coating material. As described below, the coating material may be developed to remove the non-irradiated coating material, or selectively remove the irradiated coating material, to form very smooth edges.
[0038] The radiation can be directed to the coated substrate, typically through a mask, or a radiation beam can be controllably scanned across the substrate. Typically, the radiation can include electromagnetic radiation, electron beam (beta radiation), or other suitable radiation. Typically, the electromagnetic radiation can have a desired wavelength or range of wavelengths, such as visible light, ultraviolet light, or X-rays. The resolution achievable with a radiation pattern is typically determined by the wavelength of the radiation, with higher resolution patterns typically being achievable with shorter wavelength radiation. Thus, to achieve particularly high resolution patterns, the use of ultraviolet light, X-rays, or electron beams may be desirable.
[0039] According to the international standard ISO 21348 (2007) (incorporated herein by reference), ultraviolet light extends between wavelengths of 100 nm and less than 400 nm. Krypton fluoride lasers can be used as a source of ultraviolet light at 248 nm. The ultraviolet range can be further divided in several ways under recognized standards, for example, into extreme ultraviolet (EUV) from 10 nm to less than 121 nm, and far ultraviolet (FUV) from 122 nm to less than 200 nm. The 193 nm line from an argon fluoride laser can be used as a radiation source in the FUV. EUV light at 13.5 nm is used in lithography, and it is generated from a plasma source of Xe or Sn excited by a high-energy laser or discharge pulse. Soft x-rays can be defined as 0.1 nm to less than 10 nm.
[0040] The amount of electromagnetic radiation can be characterized by a fluence or dose, which is defined by integrating the radiant flux over the exposure time. A suitable radiation fluence is about 1 mJ / cm 2 ~Approx. 175mJ / cm 2 and in a further embodiment about 2 mJ / cm 2 ~Approx. 150mJ / cm 2 and in a further embodiment about 3 mJ / cm 2 ~Approx. 125mJ / cm 2A person of ordinary skill in the art will recognize that additional ranges of radiation fluence within the explicit ranges above are contemplated and are within the present disclosure.
[0041] Based on the design of the coating material, there can be a large contrast in material properties between the irradiated areas with condensed coating material and the non-irradiated coating material with organic or carboxylate ligands substantially intact. For embodiments in which a post-irradiation heat treatment is used, the post-irradiation heat treatment can be performed at a temperature of about 45°C to about 250°C, in further embodiments from about 50°C to about 190°C, and in further embodiments from about 60°C to about 175°C. The post-exposure heating can generally be performed for at least about 0.1 minutes, in further embodiments from about 0.5 minutes to about 30 minutes, and in further embodiments from about 0.75 minutes to about 10 minutes. Those skilled in the art will appreciate that additional ranges of post-irradiation heating temperatures and times within the above stated ranges are contemplated and are within the scope of the present disclosure. This high contrast in material properties further facilitates the formation of high resolution lines with smooth edges in the developed pattern as described in the following section.
[0042] For negative imaging, the developer may be an organic solvent, such as the solvent used to form the precursor solution. In general, the choice of developer may be influenced by the solubility parameters for both irradiated and non-irradiated coating materials, as well as the volatility, flammability, toxicity, viscosity, and potential chemical interactions with other processing materials of the developer. In particular, suitable developers include, for example, alcohols (e.g., 4-methyl-2-pentanol, 1-butanol, isopropanol, 1-propanol, methanol), ethyl lactate, ethers (e.g., tetrahydrofuran, dioxane, anisole), ketones (pentanone, hexanone, 2-heptanone, octanone), and the like. Development may be performed for about 5 seconds to about 30 minutes, in further embodiments from about 8 seconds to about 15 minutes, and in further embodiments from about 10 seconds to about 10 minutes. A person of ordinary skill in the art will recognize that additional ranges within the above explicit ranges are contemplated and are within the present disclosure.
[0043] In addition to the main developer composition, the developer may include additional compositions to facilitate the development process. Suitable additives may include, for example, viscosity modifiers, solubilization aids, or other processing aids. When optional additives are present, the developer may include up to about 10 weight percent of additives, and in further embodiments up to about 5 weight percent of additives. A person of ordinary skill in the art will recognize that additional ranges of additive concentrations within the above stated ranges are contemplated and are within the scope of the present disclosure.
[0044] If the coating uses a weaker developer, such as a diluted organic developer or composition, with a slower development rate, a higher temperature development process can be used to increase the speed of the process. If a stronger developer is used, the temperature of the development process can be reduced to reduce the development rate and / or control the reaction rate. In general, the temperature of development can be adjusted between appropriate values to match the volatility of the solvent. Furthermore, the developer with dissolved coating material near the developer-coating interface can be dispersed using ultrasonic treatment during development.
[0045] Any reasonable method can be used to apply the developer to the patterned coating material. For example, the developer can be sprayed onto the patterned coating material. Spin coating can also be used. For automated processing, a puddle method can be used that involves pouring the developer onto the coating material in a stationary manner. If desired, spin rinsing and / or drying can be used to complete the development process. Suitable rinsing solutions include, for example, ultrapure water, aqueous tetraalkylammonium hydroxide solutions, methyl alcohol, ethyl alcohol, propyl alcohol, and combinations thereof. After development of the image, the coating material is disposed on the substrate as a pattern.
[0046] After the development step is complete, the coating material can be heat treated to further condense the material and further dehydrate, densify, or remove residual developer from the material. This heat treatment may be particularly desirable for embodiments in which the oxide coating material is incorporated into a final device, but may also be desirable for some embodiments in which the coating material is used as a resist and is ultimately removed when stabilization of the coating material is desired to facilitate further patterning. In particular, baking of the patterned coating material can be performed under conditions in which the patterned coating material exhibits a desired level of etch selectivity. In some embodiments, the patterned coating material can be heated to a temperature of about 100° C. to about 600° C., in further embodiments from about 175° C. to about 500° C., and in further embodiments from about 200° C. to about 400° C. The heating can be performed for at least about 1 minute, in other embodiments from about 2 minutes to about 1 hour, and in further embodiments from about 2.5 minutes to about 25 minutes. Heating can be performed in air, in vacuum, or in an inert gas environment such as Ar or N2. A person of ordinary skill in the art will recognize that additional ranges of thermal treatment temperatures and times within the explicit ranges above are contemplated and are within the present disclosure. Similarly, non-thermal treatments, such as blanket UV exposure or exposure to an oxidizing plasma, such as O2, can be used for similar purposes.
[0047] In some embodiments, adjacent linear portions of adjacent structures can have an average pitch (half pitch) of about 60 nm (30 nm half pitch) or less, in some embodiments about 50 nm (25 nm half pitch) or less, and in further embodiments about 34 nm (17 nm half pitch) or less. The pitch can be evaluated by design and can be confirmed by scanning electron microscopy (SEM), for example, top-down imaging. As used herein, pitch refers to the spatial period, or center-to-center distance, of repeating structural elements, and as commonly used in the art, half pitch is half the pitch. The feature dimensions of the pattern can also be described in terms of the average width of the features, generally evaluated away from corners, etc. Also, the features may refer to the gaps between and / or material elements. In some embodiments, the average width can be about 25 nm or less, in further embodiments about 20 nm or less, and in further embodiments about 15 nm or less. A person of ordinary skill in the art will recognize that additional ranges of pitch and average width within the above explicit ranges are contemplated and are within the scope of the present disclosure. Based on these processes, patterning can generally be adapted to form a variety of devices, such as electronic integrated circuits, by repeating the patterning process to form appropriate layered structures, such as transistors or other components.
[0048] Wafer throughput is a substantial limiting factor for the implementation of EUV lithography in high volume semiconductor manufacturing and is directly related to the dose required to pattern a particular feature. However, although chemical strategies exist to reduce the imaging dose, a negative correlation is commonly observed between the imaging dose required to print a target feature and the feature size uniformity (e.g., LWR) for EUV photoresists at feature sizes and pitches <50 nm, thereby limiting final device operability and wafer yield. Patterning capability can be expressed as a dose-to-gel value. The imaging dose requirement can be evaluated by forming a number of exposed pads, where the exposure time is stepped between pads to vary the exposure dose. The film can then be developed and the remaining resist thickness can be evaluated in all pads, for example using spectroscopic ellipsometry. The measured thickness can be normalized to the maximum measured resist thickness and plotted against the logarithm of the exposure dose to form a characteristic curve. The maximum slope of the normalized thickness vs. log dose curve is defined as the photoresist contrast (γ), and the dose value at which a tangent line drawn through this point is 1 is the photoresist dose vs. gel (D g In this way, common parameters used in characterizing photoresists can be estimated according to Mack, C. Fundamental Principles of Optical Lithography, John Wiley & Sons, Chichester, UK; pp 271-272, 2007. EXAMPLES
[0049] [Table 2]
[0050] Example 1. ((CH 3 ) 3 SnCH 2 Sn) 12 O 14 (OH) 6 (HCO2 ) 2 Preparation, Analysis, and EUV Exposure of Dodecamers Synthesis of Monomer (C 6 H 5 CC) 3 SnCH 2 Sn(CH 3 ) 3 Preparation of Dodecamer ((CH A 100 mL round bottom flask equipped with a magnetic stir bar was charged with 1.6 g of phenylacetylene and 15 mL of tetrahydrofuran. The solution was cooled to 0° C. and then 7.7 mL of a 2 M solution of isopropylmagnesium chloride in ether was added dropwise. After the addition of the isopropylmagnesium chloride solution, the resulting solution was heated to 50° C. for 10 min, followed by the removal of ether under reduced pressure. The solution after removal of ether was cooled and added dropwise to a solution of SnCl2 (1.0 g) in tetrahydrofuran (15 mL) at −40° C. The mixture was warmed to 25° C. and stirred for 14 h, followed by the addition of (chloromethyl)trimethylstannane (2 g). The solution was then stirred at 25° C. for 1 h, followed by the concentration to 4 mL under reduced pressure. Ether (20 mL) was added to the concentrated solution to form a precipitate that was collected by filtration. The precipitate was washed with ether to give 2.5 g of (C6H5CC)3SnCH2Sn(CH3)3 (Figure 1) as a white powder. This product can be further purified by recrystallization from a hydrocarbon solvent such as pentane or hexane. The -CH2Sn(CH3)3 group in this monomer structure becomes the R group in the general dodecamer structure. The product was characterized by NMR: 119 Sn NMR (500MHz, CDCl3) δ 24.42, -220.74.
[0051] SnCH 3 ) 3 Sn) 2 (OH) 12 O 14 (HCO 6 Film Deposition and EUV Contrast 2 ) 2 Example 2. Preparation and Characterization of (t-BuSn)A 10 mL round bottom flask equipped with a magnetic stir bar was charged with 1 g of (trimethylstannanyl)-tris(phenylethynyl)stannane synthesized above, 8 mL of tetrahydrofuran, and 0.1 mL of water. The solution was stirred at room temperature for 3 days. After 3 days, 0.04 mL of formic acid was added and the resulting solution was stirred for 10 minutes. The solution was then concentrated under reduced pressure, followed by the addition of ether (5 mL) to form a slurry. The precipitate was collected by filtration and dried under reduced pressure to give 0.3 g of ((CH3)3SnCH2Sn). 12 O 14 (OH)6(HCO2)2 was obtained as a white powder. The product was characterized by NMR: 119 Sn NMR (500 MHz, CDCl3) δ 19.7, -255.4, -457.16. X-ray diffraction peaks were obtained from the powder, indicating that the powder was crystalline.
[0052] (OH) 0.1142 g of the dodecamer solid from the above synthesis was dissolved by stirring in 12 mL of chloroform (HPLC >99.8%) to form a photoresist coating solution with a total Sn concentration of 0.06 M.
[0053] Thin films were deposited on silicon wafers (100 mm diameter) with native oxide surfaces. A 0.06 M precursor solution was delivered by pipette onto the substrate and spin-coated at 2000 rpm, then baked on a hotplate at 100 °C for 2 min. The film thickness was measured by ellipsometry to be 29 nm.
[0054] A linear array of 50 circular pads, each approximately 500 μm in diameter, was projected onto the wafer using EUV light on a Dose Calibration Tool (DCT) at Lawrence Berkeley National Laboratory. The pad exposure time was adjusted to deliver increasing EUV doses (8% exponential step size) to each pad. The resist and substrate were then subjected to a 2-minute post-exposure bake (PEB) on a hotplate at a selected temperature in the range of 140-200°C. The exposed and baked film was then immersed in 2-heptanone for 15 seconds and washed for an additional 15 seconds with the same developer to produce a negative tone image, i.e., remove the unexposed and low dose portions of the coating. A final 2-minute hotplate bake at 150°C completed the process. The remaining resist thickness of the exposed pads was measured using a JAWoollam M-2000 Spectroscopic Ellipsometer. Figure 2 shows the measured thickness vs. dose for each pad of four wafers that underwent PEB at temperatures ranging from 140 to 200 °C. By normalizing the thickness to the maximum measured resist thickness and plotting the normalized value vs. the log of the exposure dose, a characteristic curve for each process condition can be created. The maximum slope of the normalized thickness vs. log dose curve is defined as the photoresist contrast (γ), and the intersection of the maximum resist thickness with the tangent to the point of maximum slope defines the dose vs. gel (Dg). In this way, common parameters for evaluating photoresist performance can be obtained, and reference is made to Mack, C. (2007) Introduction to Semiconductor Lithography, in Fundamental Principles of Optical Lithography: The Science of Microfabrication, John Wiley & Sons, Ltd, Chichester, UK. Table 2 shows the ((CH3)3SnCH2Sn) 12 O 14 The contrast and Dg values of the photoresist at four PEB temperatures for (OH)6(HCO2)2 are summarized.
[0055] [Table 3]
[0056] (HCO 12 O 14 Example 3. Preparation, Analysis, and EUV Exposure of (t-BuSn) 6 and (t-BuSn) 2 ) 2 (OH) Monomeric phenylacetylide t-BuSn(CCPh)3 to dodecameric (t-BuSn) 12 O 14 (OH)6(HCOO)2 was prepared as follows: A 2 L round bottom flask (RBF) was purged with nitrogen and charged with 308 g of t-BuSn(NMe2)2 dissolved in 500 mL of pentane. The RBF was fitted with a bubbler to pass through a trap containing aqueous acetic acid. An ice bath was used to keep the temperature below 40° C. while a slight excess of phenylacetylene (337 g, 3.3 equiv.) was added dropwise. The solution was allowed to react overnight after which a crystalline precipitate formed. The t-BuSn(CCPh)3 crystals were collected and recrystallized in pentane (92% yield).
[0057] A 100 mL round bottom flask was charged with 6 g of t-BuSn(CCPh)3, 60 mL of tetrahydrofuran, and 0.6 mL of water. After homogenization, the solution was aged for 3 days, after which time crystals formed. The solution was heated to boiling and then formic acid (118 mg) was added dropwise, resulting in the formation of a precipitate. The slurry was hot filtered and recrystallized in 25 mL of methanol at -20°C (80% yield).
[0058] Single crystals were grown by recrystallization of the above clusters in n-propanol. Figure 3 shows the (t-BuSn) 12 O 14 The molecular structure of the (OH)6(HCO2)2 cluster is shown in Figure 4. 1 H (above) and 119 Sn (lower figure) NMR spectrum is shown.119 The signals at −337.03 ppm and −523.57 ppm in the Sn spectrum correspond to the penta- and hexa-coordinated Sn atoms in the molecular structure, respectively.
[0059] A small amount of (t-BuSn) 12 O 14 (OH)6(HCO2)2 (approximately 1% by weight) was dissolved in a mobile phase of 0.5% acetic acid in methanol and then injected into an Agilent 6510 QTOF mass spectrometer. 12 O 14 The peaks correspond to the (OH)6(O2CH)2 fragment: (t-BuSn) 12 O 14 (OH)6 2+ [1217u], (t-BuSn) 12 O 15 (OH)5 1+ [2434u], and (t-BuSn) 12 O 14 (OH)6·2[H2O][HOCH3][HCOOH] + [2548u].
[0060] (0 < x < 8). 12 O 14 F 8 Synthesis 12 O 14 Mass Spectrometry Analysis 8-x F x NMR Spectrum Contrast of Coating Solution, Film Deposition, and EUV Exposure In a 20 mL round-bottom flask, 0.5 g of the dodecamer (t-BuSn) obtained in the synthesis of Example 2 dissolved in 10 mL of methanol was added. 12 O 14 (OH)6(HCO2)2 was added. Approximately 7.3 parts of triethylamine trihydrofluoride (0.25 g) per dodecamer was added and the solution was allowed to stand. After one week, crystals were collected in 10% yield. (t-BuSn) 12 O 14 F8(Sn 12 C48 H 108 F8O 14 Analytical calculation for: C, 23.2; H, 4.4; F, 6.1. Result: C, 23.3; H, 4.4; F, 6.0. Addition of less than 2.67 parts triethylamine trihdydrofluoride per dodecamer produces products with smaller F:Sn ratios.
[0061] Example 4. Preparation and Film Deposition of Resist Based on (t-BuSn) The synthesis product was dissolved in methanol (approximately 1% by weight) and injected into an Agilent 6510 QTOF mass spectrometer. Figure 7 shows peaks consistent with species containing some distribution of fluorine and oxygen in the dodecamer. The most intense signal is the singly ionized deprotonated cluster [(t-BuSn) 12 O 15 (OH)F5] + The NMR spectrum is shown in Figure 8: (OH) in CDCl3 1 H, 19 F, 119 SnNMR(400MHz) is (t-BuSn) 12 O 14 A signal consistent with the F8 dodecamer is shown.
[0062] (HCOO) The fluorinated dodecamer synthesis products were dissolved in chloroform (0.035M Sn), coated onto SiO2 / Si wafers by spin coating at 1500 rpm, baked at 100°C, and exposed on an EUV Dose Contrast Tool at Lawrence Berkeley National Laboratories according to the procedure described in Example 1. After exposure, the films were baked at selected temperatures between 140-200°C (each sample has a specific temperature as specified in the figure) and then developed in 2-heptanone. The thickness of each exposed pad was optically evaluated and then plotted against the exposure dose to obtain contrast values (Figure 9). Table 3 shows the results of the (t-BuSn) 12 O 14 Parameter D derived from Figure 9 for F8 g, D0, and contrast are summarized. D0 corresponds to the starting dose for the initial increase in film thickness of the negative resist.
[0063] [Table 4]
[0064] Example 5. EUV Exposure Contrast and Line-Space Imaging of (t-BuSn) 12 O 14 (OH) 6 (HCO 2 Dodecamers (t-BuSn) Prepared according to Example 2 by dissolving 1.4735 g of Sn dodecamer in 100 mL of 10% v / v formic acid in methyl isoamyl ketone. 12 O 16 A 0.070 M Sn solution in (OH)6(HCO2)2 was prepared. Formic acid provides solution stability and improves solubility and coating quality.
[0065] Circular silicon wafers with a diameter of 10.2 cm with a native oxide surface were used as substrates for film deposition. Dodecamer films were spin-coated onto the Si wafers at 1500 RPM for 45 seconds. Selected wafers were then baked at 100°C for 120 seconds. Film thickness after coating and baking was approximately 20 nm as measured by ellipsometry. All films exhibited a root-mean-square surface roughness of <0.5 nm as measured by atomic force microscopy.
[0066] 12 O 16 2 2 ) 2 A 300 mm Si wafer with a native oxide surface was coated with the resist prepared according to Example 4. The film was spin coated at 1500 RPM and baked at 100°C for 20 seconds. The film was then exposed to extreme ultraviolet radiation on an ASML NXE:3300B scanner. An array of contrast was created in the film by projecting an 11×11 array of pads with increasing EUV photon doses for successive pads. A repeating pattern of 16 nm lines on a 32 nm pitch was also projected using dipole 90x illumination and a numerical aperture of 0.33. The exposed resist film and substrate were then post-exposure baked (PEB) for 2 minutes at selected temperatures between 120°C and 180°C on a hotplate in air. After the PEB, it was developed in 2-heptanone for 15 seconds and washed with the same developer for an additional 15 seconds to form a negative tone image, i.e., the unexposed parts of the coating were removed during development. Development was followed by a final 5 minute hotplate bake at 150° C. in air.
[0067] Line-space patterns were imaged using a Hitachi CG5000 CD-SEM. Figure 10 shows the (t-BuSn) 12 O 14 The images show resist lines formed with (OH)6(HCO2)2. Table 4 summarizes the extracted dose versus pattern size and LWR. The contrast array was analyzed by measuring the residual thickness of each exposed and developed pad by ellipsometry. Figure 11 shows the logarithm of each pad thickness normalized to the initial resist film thickness versus exposure dose, with characteristic curves shown for PEB temperatures between 120°C and 180°C. The resulting curves clearly show the negative contrast formed by the exposure, with the residual pad thickness of each resist film being near 0 nm at low doses and then increasing nonlinearly, with a linear relationship between dose and gel (D g ) reaches a maximum. It is clearly shown that the dose required to initiate the change in development rate decreases as a function of PEB. Table 4 shows the dose required for each PEB temperature. g and the derived contrast values are summarized.
[0068] [Table 5]
[0069] The above embodiments are intended to be illustrative and not limiting. Further embodiments are within the scope of the claims. Moreover, although the present invention has been described with reference to specific embodiments, those skilled in the art will understand that it may be modified in form and detail without departing from the spirit and scope of the present invention. Any incorporation by reference of the above documents is limited to not incorporating subject matter contrary to the express disclosure herein. To the extent that a particular structure, composition, and / or process is described herein as having components, elements, components, or other compartments, the disclosure herein should be understood to include those specific embodiments, embodiments that include the particular components, elements, components, other compartments, or combinations thereof, as well as embodiments that consist essentially of such particular components, components, components, or other compartments, or combinations thereof, which may include additional features that do not change the basic nature of the subject matter as suggested in the discussion unless otherwise indicated.
Claims
1. (QSn) n O 3n/2-1/2x-1/2y F x (OH) y , 1≦n≦12, (0<x+y≦8), x>0, where Q comprises an alkyl group having 1 to 16 carbon atoms.
2. The composition comprises (QSn) n O 3n/2-1/2x-1/2y F x (OH) y 2. The radiation-patternable coating of claim 1 , wherein 0<x+y≦3, x>0.
3. 3. The radiation patternable coating of claim 1 or 2, wherein Q is methyl, ethyl, n-propyl, n-pentyl, isopropyl, tert-butyl, sec-butyl, isobutyl, tert-amyl, cyclopropyl, cyclobutyl, cyclopentyl, or a combination thereof.
4. 3. The radiation patternable coating of claim 1 or 2, wherein Q is a branched alkyl group or a cycloalkyl group.
5. The Q is a tert-butyl group (—C(CH 3 ) 3 3. The radiation-patternable coating of claim 1 or 2, wherein
6. 3. The radiation patternable coating of claim 1 or 2, wherein Q is a mixture of different alkyl groups.
7. The coating has a density of 1 mJ / cm 2 ~175mJ / cm 2 3. The radiation-patternable coating of claim 1 or 2, which is patternable with a dose of EUV radiation.
8. 3. The radiation-patternable coating of claim 1 or 2, wherein the coating has a post-development contrast of 3 or greater after exposure to EUV radiation.
9. A radiation patternable coating comprising a fluorinated organotin oxo composition containing Sn-C bonds, Sn-O bonds, and Sn-F bonds.
10. 10. The radiation patternable coating of claim 9, further comprising Sn-OH bonds.
11. A radiation-patternable coated substrate comprising the radiation-patternable coating of claim 9.
12. The coated substrate of claim 11 , wherein the substrate comprises a silicon wafer.
13. The coated substrate of claim 11 , wherein the radiation patternable coating comprises a tin oxo-hydroxo network comprising Sn—C, Sn—O, Sn—OH, and Sn—F bonds.
14. The coated substrate of any one of claims 11 to 13, wherein the radiation-patternable coating has an average thickness of from 1 nm to 50 nm.
15. The coated substrate of any one of claims 11 to 13, wherein the radiation-patternable coating has an average thickness of from 3 nm to 35 nm.
16. Depositing a fluorinated organotin composition on a substrate to form a radiation patternable coating having Sn-C bonds, Sn-O bonds, and Sn-F bonds.
1. A method for forming a radiation-patternable coating on a substrate, comprising:
17. The method of claim 16 , wherein the substrate comprises a silicon wafer.
18. The fluorinated organotin composition is (QSn) n O 3n/2-1/2x-1/2y F x (OH) y , 1≦n≦12, (0<x+y≦8), x>0, where Q is an alkyl group having 1 to 16 carbon atoms or a group having the structure —CH 2 Sn(R 1 R 2 R 3 ) and is an alkyltin group having 4 to 15 total carbon atoms; R 1 , R 2 , and R 3 and each independently is an alkyl group having 1 to 5 carbon atoms.
19. The Q is a tert-butyl group (—C(CH 3 ) 3 20. The method of claim 18, wherein
20. The Q is —CH 2 Sn(CH 3 ) 3 20. The method of claim 18, wherein:
21. The fluorinated organotin composition is (QSn) 12 O 14 F x (OH) 8-x 17. The method of claim 16, comprising a composition of matter having the formula: (0<x<8), where Q is an alkyl group having 1 to 16 carbon atoms.
22. The fluorinated organotin composition is (QSn) 12 O 14 F 8 17. The method of claim 16, comprising a composition of the formula: wherein Q is an alkyl group having 1 to 16 carbon atoms.
23. The method of any one of claims 16 to 22, wherein said depositing comprises depositing a photoresist composition on said substrate comprising an organic solvent and said fluorinated organotin composition.
24. The method of any one of claims 16 to 22, wherein the depositing comprises spin coating.
25. The method of any one of claims 16 to 22, wherein the radiation patternable coating has radiation sensitive Sn-C bonds.
26. The method of any one of claims 16 to 22, wherein the radiation patternable coating comprises a tin oxo-hydroxo network.
27. The radiation patternable coating has a radiation intensity of 1 mJ / cm 2 ~175mJ / cm 2 The method of any one of claims 16 to 22, wherein the method is patternable with a dose of EUV radiation. [Others] The grounds for amending claims 1 to 28 of the present application are briefly explained below. (Claim 1-2) Claims 20 and 25 before amendment, paragraph [0013] lines 8 to 16 of the specification, and Example 3, (Claims 3 to 4) Specification paragraphs [0017] to [0018], (Claim 5) Claim 23 and Example 3 before amendment, (Claim 6) Specification paragraphs [0017] to [0018], (Claim 7) Specification paragraph [0040] lines 2-3 and Example 3, (Claim 8) Table 3 of Example 3, (Claims 9 to 11) In paragraphs [0008], [0013] lines 8 to [0015], [0027], [0035] lines 8 to 12, and [0061] to [0062] of the specification, particularly in paragraph [0013], a "Sn-C bond" is provided by tin bonded via an alkyl group, and a "Sn-O bond" is provided by tin further bridged by an oxo (O) group and / or a hydroxo (-OH) group, and O and -OH can be substituted with F to provide a "Sn-F bond". (Claim 12) Specification paragraph [0030] lines 9 to 12 and Example 3, (Claim 13) Specification paragraph [0035] lines 4 to 8, (Claims 14-15) Specification paragraph [0033] lines 5-9, (Claim 16) Claims 20 and 25 before amendment, paragraphs [0008], [0013] lines 8 to [0015], [0027], [0030] lines 1 to 2, [0035] and [0061] to [0062] of the specification, (Claim 17) Specification, paragraph [0030], lines 9 to 12 and Example 3, (Claim 18) Pre-amendment claims 20 and 25, (Claim 19) Claim 23 before amendment and Example 3, (Claim 20) Claim 24 before amendment, (Claim 21) Claims 20 (n = 12, y = 8-x, Q is an alkyl group) and 25 before amendment, and the title of Example 3 [(t-BuSn) 12 O 14 (OH) 8-x F x (0<x<8)], (Claim 22) Claims 20 (n = 12, x = 8, y = 0, Q is an alkyl group) and 25 before amendment, and the title of Example 3 [(t-BuSn) 12 O 14 F 8 ], (Claim 23) Claim 25 before amendment, (Claim 24) Specification paragraph [0031] lines 2 to 5 and Example 3, (Claim 25) Specification paragraph [0013] lines 8 to 16 and [0037] lines 4 to 14, (Claim 26) Specification paragraph [0035] lines 4 to 7, (Claim 27) Specification, paragraph [0040], lines 2-3 and Example 3. (Underlining omitted.)